Long-term Pulmonary Outcomes in Pediatric Survivors of High-risk Neuroblastoma. Issue 7 (October 2017) - Stone, Anne; Novetsky Friedman, Danielle; Worgall, Stefan; Kushner, Brian H.; Wolden, Suzanne; Modak, Shakeel; LaQuaglia, Michael P.; Wu, Xian; Cheung, Nai-Kong; Sklar, Charles A.
Abstract : Background: Children with high-risk neuroblastoma are exposed to multimodality therapies early in life and survivors confront late therapy-related toxicities. This study assessed respiratory symptoms, pulmonary function tests (PFTs), and risk factors for abnormalities among survivors. Materials and Methods: High-risk neuroblastoma survivors followed in the long-term follow-up clinic at Memorial Sloan Kettering Cancer Center were enrolled. Self-administered symptom questionnaires were completed. Medical records were reviewed for treatment information and comorbidities. PFTs included spirometry, plethysmography, and diffusion capacity of the lung for carbon monoxide (DLCO). Results: Thirty-nine survivors participated (median age at study: 11.4 y; median age at diagnosis: 2.3 y; median time since completion of therapy: 5.5 y). Chronic respiratory symptoms were reported for 33%. PFT abnormalities were identified in 79% and included low forced expiratory volume in 1 second (38%), decreased total lung capacity (44%), and abnormal DLCO (67%). PFT abnormalities were mostly mild to moderate. Mean forced vital capacity, forced expiratory volume in 1 second, and total lung capacity were normal and mean DLCO was mildly abnormal. Risks included thoracic surgery, chest radiation therapy, thoracic surgery plus chest radiation therapy, and shorter time since completion of therapy ( P <0.05). Conclusions: Although respiratory abnormalities were common, they were mostly mild or moderate. Continued pulmonary surveillance of this at-risk population is warranted. Abstract : Supplemental Digital Content is available in the text.